1996
DOI: 10.1152/ajpendo.1996.270.2.e215
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of lipolysis and lipoprotein lipase in chronically nicotine-treated rats

Abstract: These studies examined the cellular mechanisms for lower adiposity seen with nicotine ingestion. Rats were infused with nicotine or saline for 1 wk and adipocytes isolated from epididymal fat pads. Nicotine-infused rats gained 37% less weight and had 21% smaller fat pads. Basal lipolysis was 78% higher, whereas the maximal lipolytic response to isoproterenol was blunted in adipocytes from nicotine-infused rats. The antilipolytic actions of adenosine and the levels of serum catecholamines were unaffected by nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 28 publications
2
37
2
3
Order By: Relevance
“…This is different from previous findings in rats, where acute nicotine infusion increased basal lipolysis and blunted the effects of lipolytic agonists. 11 These differences are probably related to the exposure of the rats to nicotine via acute infusion, compared to cigarette smoking in humans, as well as potential differences in rat compared to human adipose cell metabolism. 25,26 The results of the present study also differ from the report that nicotine increased lipolysis measured in vivo by microdialysis, suggesting the presence of nicotinic receptors; 12 however, in that study nicotine had no effect on lipolysis in isolated human adipose cells, similar to the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This is different from previous findings in rats, where acute nicotine infusion increased basal lipolysis and blunted the effects of lipolytic agonists. 11 These differences are probably related to the exposure of the rats to nicotine via acute infusion, compared to cigarette smoking in humans, as well as potential differences in rat compared to human adipose cell metabolism. 25,26 The results of the present study also differ from the report that nicotine increased lipolysis measured in vivo by microdialysis, suggesting the presence of nicotinic receptors; 12 however, in that study nicotine had no effect on lipolysis in isolated human adipose cells, similar to the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of feeding behavior reveal that smoking or nicotine administration decreases meal size, measured as the amount of food intake per meal, without substantial changes in meal number (Blaha et al, 1998;Miyata et al, 2001). Although studies of nicotineinduced changes in overall metabolic rate are more variable (Stamford et al, 1986;Sztalryd et al, 1996), nicotine administration has been shown to alter metabolic processing in humans, intact animals and in both hepatocytes and adipocytes, in vitro (Sztalryd et al, 1996;Ashakumary and Vijayammal, 1997;Arai et al, 2001). Nicotine decreases lipolysis by inhibiting lipoprotein lipase activity, decreasing triglyceride uptake and hence lessening net storage in adipose tissue (Sztalryd et al, 1996).…”
Section: Does Nicotine Affect Feeding Via Interactions At Peripheral mentioning
confidence: 99%
“…Although studies of nicotineinduced changes in overall metabolic rate are more variable (Stamford et al, 1986;Sztalryd et al, 1996), nicotine administration has been shown to alter metabolic processing in humans, intact animals and in both hepatocytes and adipocytes, in vitro (Sztalryd et al, 1996;Ashakumary and Vijayammal, 1997;Arai et al, 2001). Nicotine decreases lipolysis by inhibiting lipoprotein lipase activity, decreasing triglyceride uptake and hence lessening net storage in adipose tissue (Sztalryd et al, 1996). Activation of nicotinic receptors also induces the expression of uncoupling protein 1 (UCP1) in both white and brown adipose tissue (Arai et al, 2001).…”
Section: Does Nicotine Affect Feeding Via Interactions At Peripheral mentioning
confidence: 99%
“…[20][21][22] Nikotin dapat meningkatkan pengeluaran katekolamin dan asetilkolin oleh sel adrenal. 23 Epinefrin dan norepinefrin selanjutnya mengaktivasi thermogenesis di jaringan lemak coklat.…”
Section: Pembahasanunclassified